Networks power: political communication in two inner city Johannesburg CBOs - Pointer, Rebecca (My University, 2021)
This research aimed to establish how two community-based organisations (CBOs) in inner city Johannesburg used communication to build political power in their political networks. As such, I explored theories on building, shaping, and transforming networks of power, especially with reference to Latour, and Deleuze and Guattari’s concept of an assemblage. Assemblages are underpinned by the desire to make connections and therefore Deleuze and Guattari’s concept of desire is helpful in revealing the connections between different elements of political communication. The departure point for this research was to examine how CBOs use political communication in networks of power or to generate networks of power. The research examined flows of communication among CBO members, their communities, and other audiences, using an a political communication machine/assemblage. The machine has five components, which were explored in depth in the chapters of this thesis. They are: desire, framing, aesthetics, communication tools and audiences. Desire is not a lack but the creative, productive impetus for the organisations; using this theory to explore the two CBOs communications led to insights into the not only the material outputs and conditions of communication, but also both the rational and affective qualities of that communication. In terms of the study of communication, the conceptual framework allowed for the study of the different components working together to generate a communication flow, instead of simply relying on a static study of frames, or tools, or aesthetics or audiences. As such, the study reveals the dynamism in CBO political communication. Previous studies of South African CBOs have mentioned that before CBOs protest, they undertake extensive efforts to communicate with government; however, the previous studies did not elucidate what these extensive efforts consisted of, so this study has provided rich detail for further exploring the dynamic. The two CBOs were markedly different in their structure and their efforts to communicate. The Inner City Resource Centre (ICRC), which tackles housing issues in the inner city, was well funded, and had offices. Their communication efforts were highly effective at building and retaining its core membership. However, they were not successful in connecting with the City of Johannesburg, because the city had locked them out of participatory spaces. One Voice of All Hawkers Association (One Voice) was highly fractious, some members exhibited micro-fascisms, and the organisation ran in somewhat of a haphazard pattern in its efforts to protect street traders. However, they were highly successful at micro-local politics, using subterfuge to undermine the city’s trader administration system and preventing traders from being evicted. One Voice also sustained a large membership base over a long period of time, and this was mainly based on one-on-one communication. Their success was not based on a powerful political communication machine, but instead on the way they opportunistically managed micro-local circumstances. The study showed that an effective political communication machine was important for growing solidarity networks. However, large parts of government could not be reached, regardless of what communication strategies the organisations deployed, since participatory governance spaces were either closed off or inaccessible.
A thesis submitted in fulfilment to the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, School of Economics & Finance, University of the Witwatersrand, 2021
Keywords: Public communication; Community-based organisations; Collective action frames; Aesthetics; Communication tools; UCTD; SDG-9: Industry, innovation and infrastructure